Augmented Reality and Tourism: utilizing Technology to enhance culture and history - Santos, Waldsson Sacramento dos (2025)
Innovative technologies, such as Augmented Reality, emerge as a powerful tool to engage visitors with the historicity of tourist locations. In this sense, this article presents the experience of two authors in the application of Augmented Reality (AR) to promote and preserve the historical heritage of Penedo-AL, as a way to encourage local tourism. The theoretical framework of this study considers the preservation of public heritage or the use of interactive technologies and immersive experiences to promote tourism and educational engagement. The methodological approach used is based on an experience report, structured in three stages: i) field research to collect the history and photos of tourist locations; ii) organization of the collected materials in video format; and iii) development of the AR solution using ReactJs, AR.js and Python technologies. The validation of the product of this study was presented in two cultural events: the Cinema Circuit and a cultural exhibition at IFAL in the city of Penedo-AL. The main results detail the experience of two users, which demonstrate good use of the technology, reinforcing its potential as an educational and tourist tool. The study concluded that RA can contribute significantly to the valorization and preservation of historical heritage, encouraging new forms of learning and tourism.